Identifying Organizational Factors Affecting Assessment Policy Adherence in Higher Education - Mardani, Mojgan; Ranjkesh, Ashkan (Assessment and Practice in Educational Sciences, 2023)
This study aimed to identify and analyze the organizational factors that influence adherence to assessment policy in higher education institutions. A qualitative research design was employed to explore institutional and cultural dynamics affecting assessment policy implementation. Twenty participants, including academic staff and administrators from various universities in Tehran, were selected using purposive sampling. Data were collected through semi-structured interviews and continued until theoretical saturation was reached. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo software. Thematic analysis followed an inductive coding process involving open, axial, and selective coding to extract key patterns and relationships within the data. The analysis revealed three overarching themes: leadership and governance, institutional culture and values, and structural and resource constraints. Within the domain of leadership and governance, participants highlighted issues such as inconsistent policy communication, weak accountability mechanisms, and limited decision-making transparency. Institutional culture factors included faculty resistance to standardization, informal peer norms, ethical dilemmas, and departmental autonomy that often conflicted with formal guidelines. Structural and resource constraints such as lack of assessment training, limited support systems, excessive administrative workload, and fragmented monitoring infrastructures were also identified as major impediments to policy adherence. Participants emphasized that policy implementation is shaped by a complex interplay of formal directives and informal institutional realities. Adherence to assessment policy in higher education is influenced by a combination of leadership engagement, organizational culture, and operational capacity. To improve implementation, institutions must align policy with local practices, invest in faculty development, ensure clarity and accessibility of guidelines, and foster a culture of shared responsibility and ethical accountability in assessment processes.